Antimicrobial and phytochemicals properties of arenga pinnata / Nadiah Aisyah Bukari - Bukari, Nadiah Aisyah (Faculty of Applied Sciences, 2015)
Bacterial resistance towards presence antibiotics causes the need for new drugs especially from natural resources. Arenga pinnata is a native plant from Kuala Pilah and the lack of study of this plant in antimicrobial activity is resolved here. The study aim to determine the antimicrobial properties of dry and fresh methanolic extract of A. pinnata and to determine the phytochemical compound in A.pinnata. The result of the study showed that dry methanolic extract of A.pinnata show very little antimicrobial activity towards two Gram positive bacteria(Bacillus subtilis and Staphylococcus aureus) and one Gram negative bacteria(Escherichia coli). The fresh methanolic extract of A. pinnata showed noantimicrobial activity on any bacteria. Qualitative phytochemical tests for dry andfresh methanolic extract of A. pinnata was tested and alkaloids and terpenoidswere detected on dry extract while only terpenoids were detected on fresh extract.In conclusion, A. pinnata has a low potential to be a new antibiotics.